Skrening Bakteri Asam Laktat yang Diisolasi dari Usus Ayam Broiler sebagai Kandidat Probiotik untuk Unggas - Anwar Rosyidi; Muhamad Ali; Nurbaiti Nurbaiti (Faculty of Animal Husbandry, University of Mataram, 2016)
The use of probiotics is increasingly popular as an alternative replacement to antibiotic uses in stimulating healthand growth of broiler chickens. The use of antibiotics may disturb the balance of the gut microbiota and play asignificant role in the emerging of antibiotic resistance pathogens. Thus, the objective of this study was to isolateand screen lactic acid bacteria (LAB) from the intestine of broiler chickens as probiotic candidates. LAB wereinitially screened by phenotypic assay. Furthermore, those strains which belonged to LAB were screened forinhibitory activity against E. coli. Results showed that a total of 4 isolates were considered as members of lacticacid bacteria indicating by the results of phenotypic assays: gram positive, catalase and oxidase negative, and ableto perform carbohydrate fermentation. Out of the 4 isolates, only one isolate showed an inhibitory activity againstthe targeted pathogen. Further research is still needed to confirm the potential strain for probiotic in poultry.